Communication Strategy for The E-Tilang Program at The Cirebon City Police Department - Salsabila Dwiyanti; Sri Wulandari; Welly Wihayati (Siber Nusantara Research, 2026)
An effective communication strategy is needed to ensure that traffic law enforcement is understood by the public; to this end, the E-Tilang programme has been introduced as a technology-based public service innovation. This study aims to analyze the communication strategies of the E-Tilang program at the Cirebon City Police Department and to identify supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative with a descriptive approach. Data were collected through in-depth interviews with key informants, namely traffic police officers from the Cirebon City Police Department, and supporting informants from the public who are users of the E-Tilang program. The research results indicate that the communication strategies for the E-Tilang program include conveying information through direct interaction in the field and via the official social media channels of the Cirebon City Police Department. These strategies are effective in introducing the program and increasing public compliance; however, the public’s understanding of the technical mechanisms of E-Tilang remains limited. Factors supporting the effectiveness of communication strategies include the quality of message delivery, communicator-recipient interaction, media usage, and the effects/feedback from recipients.